2022
DOI: 10.1111/apm.13269
|View full text |Cite
|
Sign up to set email alerts
|

Human lung vascular endothelium may limit viral replication and recover in time upon the infection with rhinovirus HRV16

Abstract: Vascular endothelium is a semi‐permeable barrier that regulates the flow of nutrients, ions, cytokines and immune cells between blood and tissues. Barrier properties of endothelium, its ability to regenerate and the potential for secretion of inflammatory mediators play a crucial role in maintaining local tissue homeostasis. The lung vascular endothelial cells were shown to be infected by human rhinovirus (HRV) and generate antiviral, inflammatory and cytopathic responses. The current study reveals that in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Lung-derived human microvascular endothelial cells (HMVEC-Ls) demonstrated distinct loss of endothelial barrier integrity resulting in depleted cadherin expression and induced permeability after RV-A16 exposure. This may be associated with increased apoptosis that was also observed or possibly broad dysfunction of the endothelium that transiently prevented proliferative and migratory capacity of exposed cells [ 162 , 163 ]. Vascular permeability in response to RV exposure may enable trans-endothelial migration of circulating immune cells into airway-adjacent tissue and may exaggerate airway inflammation [ 164 ].…”
Section: Structural Cells Of the Airwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Lung-derived human microvascular endothelial cells (HMVEC-Ls) demonstrated distinct loss of endothelial barrier integrity resulting in depleted cadherin expression and induced permeability after RV-A16 exposure. This may be associated with increased apoptosis that was also observed or possibly broad dysfunction of the endothelium that transiently prevented proliferative and migratory capacity of exposed cells [ 162 , 163 ]. Vascular permeability in response to RV exposure may enable trans-endothelial migration of circulating immune cells into airway-adjacent tissue and may exaggerate airway inflammation [ 164 ].…”
Section: Structural Cells Of the Airwaymentioning
confidence: 99%
“…Upon RV exposure, HMVEC-Ls also produced strong inflammatory responses, including Th2 cytokines IL-4 and IL-13, that may promote remodeling cascades within lung microvasculature or other airway structural cells [ 161 ]. Notably, direct infection of HMVEC-Ls induced the upregulation of VEGFA , ANGPT1 (angiopoietin-1), and FGF2 gene expression, as well as upregulation of VEGF receptor genes FLT1 , KDR , and NRP1 [ 163 ]. Importantly, the upregulation of both proangiogenic mediators and receptors in HMVEC-Ls may enable a feed-forward signaling loop that promotes endothelial remodeling and neovascularization near airways.…”
Section: Structural Cells Of the Airwaymentioning
confidence: 99%
“…In our previous studies, we have shown that rhinovirus HRV16 infection of the human lung vascular endothelium induced a strong inflammatory cytokine and Type I and III IFN synthesis accompanied by an upregulation of OAS‐1 and PKR mRNA expression [2, 4]. We also proved the ability of HRV16‐infected endothelium to restore and gain its barrier capacities [8]. OAS‐1 and PKR are IFN‐dependent agents that may be directly involved in the inhibition of viral replication by degrading viral RNA and suppressing the translation of major structural viral proteins, such as capsid proteins.…”
mentioning
confidence: 99%